Training in Highland Vegetable Cultivation Using Verticulture Method in The Arafah Permai Housing in Koto Panjang Town, Padang Panjang - Indra Hartanto (Pelita Eksakta, 2018)
The increasing number of human populations will certainly reduse the amount of productive land, especially in urban areas. Food consumption needs that continue to increase but not offset by production will certainly threaten human survival. The narrower of productive land especially in urban areas certanly requires a way to maximize the limited use of land in order to remain productive, one of which is the cultination of plants with a verticulture system. Padang Panjang city include highland temperate rigion, therefore many vegetable can grow and develop in this area like cale, pakcoy and lettuce. No exeption for Arafah Permai housing which is located in Padang Panjang city with a farm/ narrow yard that is suitable for cultivation systems using this verticulture method.